The influence of sport climbing on depression and anxiety levels - literature review - Zieliński, Grzegorz; Byś, Aleksandra; Baszczowski, Michał; Ginszt, Michał; Suwała, Marta; Majcher, Piotr (Journal of Education, Health and Sport, 2018)
Introduction: Depression, as one of the most common psychological disorders, which is characterized by anxiety problems, lack of energy, feeling of worthlessness or self-esteem problems affects from 5 to 17% of the population. Despite the fact that it is such a vast problem, standard methods of treatment are usually unsatisfactory and relatively not universally accessible. For these reasons, it is crucial that some alternatives to traditional methods of depression treating, such as physical activity should be pursued. Methods and materials: The main study material of our research consisted of publications, which were found in PubMed, ResearchGate and Google Scholar databases. The first stage of the research was to find publications from the last 5 years and review the mentioned titles. The second stage was to conduct an overview of the abstracts as well as entire texts. Based on these criteria, four publications have been qualified for the study. Results: The overview of the literature indicates that despite the differences in methodology, size and age of the study groups, some comparable conclusions when it comes to the effectiveness of practicing climbing on the process of regulating emotions can be drawn. What is more, practicing climbing can benefit depression treatment by controlling the feeling of fear and anxiety, which may also occur during depression. Conclusions: The research suggests that sport climbing can positively influence the reduction of the depression and anxiety levels as well as maintain emotional stability. Further research should be carried out on the question of whether it is sport climbing as a particular sport that influences the reduction of depression and anxiety levels, or is any other form of physical activity equally influential when it comes the reduction of these disorders.